NILAI RELIGIUS DALAM LIRIK LAGU MELAYU JAMBI PADA ALBUM MAYANG MANGURAI KARYA SYAHRIL JAHARI - Mhd. Redho Kurniawansyah (Universitas Batanghari, 2020)
This research aims to describe the aspects of faith between human and God (Hablumminallah) which is found in Jambi Malay song lyrics on the album Mayang Mangurai by Syahril Jahari. The type of research used in this research is qualitative descriptive. The data of this research is the lyrics of Jambi Malay songs on the album Mayang Mangurai by Syahril Jahari. The data shows that each of the song lyrics signified the quotation of religious values relating to the relationship of human with God (Habluminallah). Based on the analysis, it can be seen that there are several aspects found in that song lyrics in which 28 quotations derived from the aspect of faith in God. This represents how people have faith in God. Based on the analysis, it can also be concluded that the lyrics of Jambi Malay songs on the album Mayang Mangurai by Syahril Jahari contain religious values related to human relationship with God (Hablumminallah) from the persepctive of God’s blessing towards human being.